Mapping the Farm; Iowans Who Made a Difference; American Farms: Exploring Their History - Ted Hutchcroft (Journal of Applied Communications, 1997)
Reviews of Mapping the Farm, by John Hildebrand; Iowans Who Made a Difference, by Don Muhm and Virginia Wadsley; American Farms: Exploring Their History, by R. Douglas Hurt.